Green Economic Development: A Systematic Literature Review - Ismail, Ismail; Khairunisah, Khairunisah; Maharani, Bunga Hilda; Ardila, Wulan Rekah; Suparman, Suparman; Al-Ifansyah, M. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This article explores the development of green economy research topics and issues. Using the Systematic Literature Review (SLR) method and data analysis using the VOSviewer application on 482 articles from Scopus, the study found that Wang J. is the most prolific researcher contributing to the issue of environmental pollution, carbon emissions, and green tourism. Companies facing financial performance bottlenecks due to green innovation can address this issue by increasing executive equity incentives and reducing the pay gap between management and employees. New researchers such as Ozturk I., Ullah S., Li X., and Wu H. contribute to green innovation and agriculture, finding that reduced pesticide use does not lower agricultural productivity. Globally, China successfully implemented a green economy through strict environmental regulations and large investments in renewable energy. Topic cluster analysis revealed that Economic Growth and Circular Economy are the main issues, while Price, Barrier, Green Practice, Financial Inclusion, and Green Development are the focus of recent studies, especially in the application of green bonds and financial inclusion. These developments form a strong basis for the implementation of green economy concepts globally.